PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 KOTO XI TARUSAN - Wahyuni, Mega; Delsi K, Delsi K; Haryono, Yulia (Pendidikan Matematika, 2014)
ABSTRACTThe aim of this research was to reveal whether the mathematics conseptual understanding of the students taught by using Talking Stick cooperative learning model was better than that of students taught by using conventional learning. This was an experimental research which used random toward the subject design. The population of this research was all of students in class VIII of SMPN 2 Koto XI Tarusan registered in academic year 2013/2014. The instrument of the research was a test whose reliability was 0,813. The data gathered was analyzed by using t-test assisted with MINITAB. Based on the result of data analysis it was found that P-value (0,000) was smaller than Î± = 0,05 indicating that the mathematics conceptual understanding of the students taught by using Talking Stick cooperative learning model was better than that of students taught by using conventional learning in class VIII of SMPN 2 Koto XI Tarusan.